Green Fabrication of Titanium Dioxide Nanoparticles and their Antimcrobial and Anticancer Activities - Parveen, Shama; Kandwal, Anuj; Rao, C. Narasimha; Kumar, D. Veera Nagendra (Asian Journal of Chemistry, 2023)
In this study, a plant-mediated method for the synthesis of titanium dioxide (TiO2) nanoparticles is reported. Using the titanium oxide and a plant extract of medicinal herb Leucas cephalotes, the TiO2 nanoparticles were effectively synthesized. The reaction temperature was kept between 75 ºC and 80 ºC, while 1 M of TiO2 and the plant extract were being processed. The absorption peak for titanium dioxide nanoparticles in the UV-Vis spectrometer was observed at 212 and 345 nm. The typical dimension of the nanoparticles was determined to be 38.99 nm from the XRD pattern. According to the findings, titanium and oxygen were composed with high energy signals of 61.27% and 23.16%, respectively. According to FT-IR spectrum, the Ti-O bonding absorption peak is appeared at 586 cm-1. The scanning electron microscopy (SEM) was employed to confirm the spherical shape of the synthesized TiO2 nanoparticles. The green synthesized TiO2 nanoparticles could be used to treat a variety of malignancies. The MTS and MTT assays were used to assess the anticancer activity of biogenic TiO2 nanoparticles. The IC50 values were 1.89, 2.00, 1.98 and 4.00 μM, respectively, against the MCF-7, HeLa, PC-3 and A549 nanoparticles cancer cell lines. Additionally, this study has also shown that synthesized TiO2 nanoparticles are highly active against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa and Escherichia coli as well as against yeast (Candida albicans).